Vases, Caskets, and Decorative Lamps of the Leningrad Factory of Porcelain in 1956–1966: Context, Attribution, Interpretation - Sapanzha, Olga S. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2021)
This paper focuses on two stages in the development of post-war production interior porcelain. The first stage is the completion of the development in the decorative and industrial arts of the grand style. The second stage is the development of modern style, which is reflected in the works of mass porcelain. The research refers to the Leningrad Factory of Porcelain and the production of the enterprise from 1956–1966. The products of the plant have not been studied sufficiently so far. However, the factory was one of the many Soviet porcelain enterprises that was involved in the creation of a new living environment. Two stages in the development of industrial art related to the organisation of the residential interior were reflected in the company’s products, i.e. works of small porcelain plastics, utilitarian porcelain, i.e. vases, boxes, bottles, night lamps, etc. The first stage is filled with works of small plastic arts (second half of the 1950s). The second stage is associated with the interior, in which porcelain goods played the role of accents in the interior, emphasising empty space (first half of the 1960s). The author of the article carries out analysis of caskets and vials of the enterprise (40 Years of October caskets, casket with a lion, Matryoshka casket, Summer Garden, a series of bottles and caskets), vases and pots (Lines planters, decorative vases, damask, and stacks), lamps (Chinese Pagoda night light, Golden Cockerel night light). Based on the interpretation of the value of the enterprise in the formation of the interior, the value of products in the processes of transition from the grand style to the modern style, a conclusion is drawn about the importance of the plant in the formation of the living environment. The massive nature of the works of the plant influenced the fact that the current stylistic trends were available to a vast number of Soviet citizens, who perceived new aesthetic norms.